Memory Binding Test and Its Associations With Hippocampal Volume Across the Cognitive Continuum Preceding Dementia - Markova, Hana; Fendrych Mazancova, Adela; Jester, Dylan J; Cechova, Katerina; Matuskova, Veronika; Nikolai, Tomas; Nedelska, Zuzana; Uller, Miroslav; Andel, Ross; Laczó, Jan; Hort, Jakub; Vyhnalek, Martin (Assessment, 2023)
Innovative memory paradigms have been introduced to capture subtle memory changes in early Alzheimer's disease (AD). We aimed to examine the associations between different indexes of the challenging Memory Binding Test (MBT) and hippocampal volume (HV) in a sample of individuals with subjective cognitive decline (SCD; n = 50), amnestic mild cognitive impairment (aMCI) due to AD (n = 31), and cognitively normal (CN) older adults (n = 29) recruited from the Czech Brain Aging Study, in contrast to traditional verbal memory tests. Both MBT free and cued recall scores in immediate and delayed recall conditions were associated with lower HV in both SCD and aMCI due to AD, whereas in traditional verbal memory tests only delayed recall scores were associated with lower HV. In SCD, the associations with lower HV in the immediate recall covered specific cued recall indexes only. In conclusion, the MBT is a promising test for detecting subtle hippocampal-associated memory decline during the predementia continuum.
Keywords: Dementia; Memory, Short-Term; krátkodobá paměť; hipokampus; rozpomínání; medial temporal lobe atrophy; demence; lidé; subjective cognitive decline; Mental Recall; kognice; free and cued verbal memory; Alzheimer’s disease; Aged; semantic memory binding; mild cognitive impairment; Cognition; Hippocampus; senioři; challenging tests; Humans